Living Lab services promoting health in the community through participation - Holopainen, Arto; Kämäräinen, Pauliina; Kaunisto, Merita; Kekäläinen, Heli; Metsävainio, Kirsimarja (Finnish Journal of eHealth and eWelfare, 2018)
In the time of urban growth, people should be at the heart of development, too often they are forgotten. However, growth poses also a great possibility. Cities can transform into open innovation Living Labs, places to experiment and co-create with creative ideas to improve people’s health and wellbeing. Open innovation Living Lab is one-step for city towards smart and healthy society. This requires bold political choices, strategic level approach, open-minded governance and new operational models. The City of Kuopio has taken this opportunity into action together with Kuopio University Hospital. Living Lab operates as an authentic co-creation environment to enable collaboration between citizens, industry, academia and public sector (Quadruple Helix Open Innovation model). This was implemented through primary health care services bringing together community and citizens´ homes for co-creation of new solutions, which helps people, live longer in their homes and increase the quality of life. The elderly and their close relatives have been enthusiastically involved in the services. Participation opportunities and the feeling of social cohesion have increased. Critical success factors are support from strategic level, well-coordinated services, governance, a broad customer base and solutions made from the genuine need. Collaboration between all stakeholders has made it possible to provide better products and services that can improve health and wellbeing of the community in all sectors of life. At the same time, it promotes citizens’ participation and supports co-creation of new ideas arising from the community and the growth of healthy city.